The Pretreatment Effect of Single Culture White Rot Fungi on the Anatomical Structure of Betung Bamboo - Widya Fatriasari; Ratih Damayanti; Sita H Anita (Masyarakat Peneliti Kayu Indonesia, 2012)
This study was to investigate the changes of morphological, macroscopic and microscopic characteristic on betung bamboo fiber during single culture of white rot fungi pretreatment. Fresh, and bark less 2 years old betung bamboo (Dendrocalamus asper) chips, 1.6 cm in length were inoculated by 10% of white-rot fungi inoculums stock for 30 and 45 days in room temperature. This study used three kinds of fungi i.e Trametes versicolor, Pleurotus ostreatus and Phanerochaete chrysosporium. After the incubation period was finished the chips were separated by maceration process (Schutze method) to analyze the fiber dimension and its derived value. The fibers were then observed the macroscopic and microscopic structure by optical microscope. The pretreatment caused the decreasing of fiber length, cell wall thicknesses, while the lumen and fiber diameter were since in versa. The improvement on fiber derived value except muhlsteph ratio was found in this study. Bamboo pretreated by T. versicolor for 30 days showed the best fiber dimension and fiber derived value and the treated bamboos were predicted to produce pulp with superior grade quality (grade I).Key words: bamboo structure, betung bamboo, fiber dimension, white rot fungi